Aporocotyle mariachristinae n. sp., and A. ymakara Villalba & Fernández, 1986 (Digenea: Aporocotylidae) of the pink cusk-eel, Genypterus blacodes (Ophidiiformes: Ophidiidae) from Patagonia, Argentina - Hernández Orts, Jesús Servando (2012)
Aporocotyle mariachristinae n. sp. and A. ymakara Villalba & Fernández, 1986 were collected from the bulbus arteriosus and ventral aorta of pink cusk-eels, Genypterus blacodes (Forster, 1801) from Patagonia, Argentina. A. mariachristinae n. sp. can be distinguished from all the species of Aporocotyle by the asymmetrical extension of posterior caeca (right posterior caecum longer, terminating at the area between mid-level of ovary and posterior body end; left posterior caecum shorter, terminating at the area between mid-level of cirrus sac and posterior to reproductive organs), the distribution of spines along the ventro-lateral body margins and the number of testes. The new species clearly differs from A. ymakara, from the same host species, in the esophagus / body length ratio, the absence of distal loops at caeca, the anterior caeca / posterior caeca length ratio, and the number of testes. Additionally, in A. ymakara the left posterior caecum may be longer than right posterior caecum, while in the new species left posterior caecum is always shorter. The specimen of A. ymakara collected from Argentina is also described. We also provide observations of the distribution of spines in different species of Aporocotyle, including new specimens of A. argentinensis Smith, 1969 from Merluccius hubbsi Marini, 1933. Molecular sequence data obtained from partial 18S and 28S rDNA regions were compared between the new species and other two species of Aporocotyle (A. argentinensis and A. spinosicanalis Williams, 1958). This is a new locality record for A. ymakara, extending the known geographical distribution for this species from Chile to Argentina, and the first report of two species of Aporocotyle in the same host species and locality.